UPAYA MASYARAKAT WAYKANAN DALAM MENGATASI PANDEMI DAN PENGUATAN PEMBELAJARAN DARING AGAR BERJALAN EFEKTIF - Rinaldo, Rico Rolan; Fasa, Muhammad Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2022)
The purpose of this research is to find out the community's efforts in overcoming the pandemic and strengthening online learning during the pandemic. Covid-19 has a broad impact on various sectors, including agriculture, education, and other MSMEs that affect food availability and distribution. Strengthening local food productivity at the household or community scale is the key to anticipating food shortages. This study uses a quantitative descriptive approach, data obtained from journals, interviews, and field observations. The selection of respondents used purposive sampling with inclusion criteria, namely community houses and education personnel